1971
DOI: 10.1097/00006842-197109000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Autonomic Responsivity in the Adult Rat

Abstract: Compared with undisturbed controls, rats handled on Days 1-7 of life exhibited diminished cardiac response to handling and to novel stimulation at 100 days of age. Previous handling had a greater effect in females. Defecation scores were significantly reduced by prior handling, although correlation between measures of heart rate and defecation frequency was not significant. Between the groups, behavioral measures did not appear to be responsible for differences in heart rate. In adulthood, females had higher h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…Sex differences in cardiovascular responses to manipulation of early experience and to subsequent stressors also modulate the influence of environmental conditions on regulatory functioning. For example, Blizard (1971) observed that, among rats handled daily prior to weaning (at 21 days), attenuation of the expected tachycardia during openfield testing was greater in females than in males. Henry, Meehan, and Stephens (1967) reported that, when subjected to chronic psychosocial stress, male mice of the CBA strain developed sustained hypertension, while the blood pressures of females remained within the normal range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences in cardiovascular responses to manipulation of early experience and to subsequent stressors also modulate the influence of environmental conditions on regulatory functioning. For example, Blizard (1971) observed that, among rats handled daily prior to weaning (at 21 days), attenuation of the expected tachycardia during openfield testing was greater in females than in males. Henry, Meehan, and Stephens (1967) reported that, when subjected to chronic psychosocial stress, male mice of the CBA strain developed sustained hypertension, while the blood pressures of females remained within the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…TUCKER AND JOHNSON tally shaped aspects of the cardiovascular and behavioral reactivity observed among SHR rats. For this purpose, a neonatal handling procedure, previously shown to attenuate the behavioral and physiological reactivity of rodents to a variety of environmental conditions (e.g., Ader, 1975;Blizard, 1971;Denenberg & Zarrow, 1971;Levine, Haltmeyer, Karas, & Denenberg, 1967;Levine & Mullins, 1966;Whimbey & Denenberg, l966,1967a, b ), was used to modify response patterns subject to alteration by early experience. This design allowed critical examination of the hypothesized, but as yet unproven (Tucker & Johnson, 1 98l), association between behavioral and cardiovascular hyperresponsiveness within the SHR strain.…”
mentioning
confidence: 99%
“…Withal, there is scant evidence for an influence on cardiovascular function: adult rats handled as neonates are reported to have a reduced heart rate response to novel stimulation (Blizard, 1971). Suggestive of a maternal influence, correlation analysis indicates that differences in behavioral interactions between rat mothers and pups contribute to variance in adult blood pressure (Myers et al, 1989).…”
mentioning
confidence: 99%
“…These "disruptive early experiences," such as exposure to temperature extremes or electric shocks, have been reported to alter adult behaviors, including open-field activity, active-avoidance, startle' responses, and "emotionality"' (6)(7)(8). Disruptive early experience also affects several neuroendocrine -parameters that involve the hypothalamic-pituitary-adrenal response to stress (5,9,10 (12)(13)(14). Con of mean) between groups of rats given cold treatment on postnatal day 1 (0) and untreated controls (-) when tested for three consecutive days as adults at about 240 days of age.…”
mentioning
confidence: 99%
“…One important aspect of disruptive experience is that it must occur early in life in order to have profound consequences (6). We tested this notion of a "critical period" by administering cold treatment on either postnatal day 6 or day 10. Treatment on day 6 brought about elevations in 5HT levels in the fore-and midbrain in both sexes on day 17, as shown in Fig.…”
mentioning
confidence: 99%